The perceived coolness of using virtual reality technology in blended learning performance can improve learning motivation and learning satisfaction - Liu, Xiaojun; Zhang, Hui; Liu, Liang (Frontiers in Education, 2024)
This study verifies the practical use of virtual reality (VR) technology in real-world educational settings. The evidence indicates that the unique encounter provided by technology can assist university scholars in mastering educational assignments with high motivation and satisfaction towards the innovative learning system. This study analyzes 82 graduate students who used VR technology in the classroom for six weeks. The collected data were further analyzed using SPSS24.0 and SMARTPLS 3 analysis software. The study found the use of VR technology in education led to high levels of satisfaction and motivation to learn. As a result, college students' learning performance was improved. The research also found that learning motivation and satisfaction played a partial role in mediating the correlation between perceived coolness and blended learning performance. This finding highlights the importance of the blended learning task arrangement, which was further verified through actual learning tasks.